1996
DOI: 10.1111/j.1600-0722.1996.tb00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Lessening dental erosive potential by product modification

Abstract: Current interest in dental erosion has led to increasing attention to ways in which potentially erosive products might be modified. Information on how this could be achieved has been hard to gather, and has focused chiefly on possibilities in reformulating soft drinks. The bulk of the work published on this relates to calcium and phosphate supplementation, ranging from early experimentation on saturation of a demineralising medium with tricalcium phosphate, through tests of more soluble phosphates and other ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
19

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 25 publications
1
75
0
19
Order By: Relevance
“…18 The purpose of this in vitro study was to assess the capacity of six brands of carbonated drinks to bring about dental erosion and determine if the addition of milk affected this. It was not the primary aim of this work to make inter-drink brand comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…18 The purpose of this in vitro study was to assess the capacity of six brands of carbonated drinks to bring about dental erosion and determine if the addition of milk affected this. It was not the primary aim of this work to make inter-drink brand comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Most studies have shown that when drinks that contain fermentable carbohydrate are consumed, there is a drop in the pH of the dental plaque in vivo. The production of acid by bacteria in such close proximity to the tooth surface would mean that on consumption enamel demineralisation could occur, hence their cariogenic potential.…”
Section: Subject Selectionmentioning
confidence: 99%
“…This increases the erosive potential of these drinks, at least when measured in vitro. 40 A successful attempt to reduce the erosive potential of soft drinks by the addition of calcium citrate-malate was reviewed by Grenby 30 but a later in vivo investigation by Rugg-Gunn et al 41 found no difference in the amount of erosion seen in enamel slabs treated with plain or modified orange drinks. One of the potentially most important steps in soft drink modification has been the development and subsequent marketing of Ribena Tooth Kind.…”
Section: Drink Modificationmentioning
confidence: 99%
“…30 Addition of calcium lactate to Coca Cola® has been shown to reduce the erosive potential of this most international of erosive beverages 39 but this research does not appear to have been taken up by the manufacturer. Rather the reverse trend is seen with the marketing of drinks with added citric acid to drinks such as Pepsi Cola® and to several diet preparations of carbonated drinks.…”
Section: Drink Modificationmentioning
confidence: 99%
See 1 more Smart Citation